2007
DOI: 10.1007/s00464-007-9530-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrotomy closure using bioabsorbable plugs in a canine model

Abstract: The repair of gastric perforation commonly involves simple suture closure using an open or laparoscopic approach. An endolumenal approach using prosthetic materials may be beneficial. The role of bioprosthetics in this instance has not been thoroughly investigated, thus the authors evaluated the feasibility of gastric perforation repair using a bioabsorbable device and quantified gross and histological changes at the injury site. Twelve canines were anesthetized and underwent open gastrotomy. A 1-cm-diameter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…19,20 A self-expandable metallic vascular occluder has been used successfully experimentally for closure of an access viscerotomy. 21 A biointegrative and absorbable material can avoid a permanent and potentially contaminated foreign body, which may impair healing.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 A self-expandable metallic vascular occluder has been used successfully experimentally for closure of an access viscerotomy. 21 A biointegrative and absorbable material can avoid a permanent and potentially contaminated foreign body, which may impair healing.…”
Section: Discussionmentioning
confidence: 99%
“…On histologic examination, there was robust initial ingrowth through 8 weeks and eventual attenuation, possibly reflecting collagen turnover and remodeling at 12 weeks, as would be expected in the accepted time course of wound healing with healthy subjects. 2 Similarly, in a rat gastric perforation model, a porcine-derived small intestine submucosal patch was used successfully for closure in all animals. Histologic examination revealed the patch to be an effective scaffolding agent, as evidenced by early regeneration of normal gastric mucosa at its edges.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a recent study, we demonstrated that the application of a bioabsorbable plug device resulted in durable closure of gastric perforation with physiologic healing of the injury site in all animals. 2 Other simple closure techniques involve the use of endoscopic clips or loops, although these only offer mucosal reapproximation. 3,4 Full-thickness endoscopic suturing and stapling devices are currently under study and have generally been successful in closing gastrotomies after endoscopic transgastric peritoneoscopy.…”
mentioning
confidence: 99%
“…19,20 This eliminated the need for complex tissue manipulation and provided watertight closure with minimal infectious complications. This technique might simplify the process of viscerotomy closure, provided that it is as reliable as a full-thickness tissue approximation.…”
Section: Laboratory Achievements To Datementioning
confidence: 99%